PENGARUH VARIASI FRAKSI VOLUM SERAT TANDAN KOSONG KELAPA SAWIT DAN SERAT AMPAS TEBU TERHADAP KEKUATAN TARIK KOMPOSIT HYBRID BERMATRIK POLYESTER - Fajar Paundra; Khairul Imad; Abdul Muhyi; Opi Sumardi; Setiyo Rojikin (LPPM Politeknik Manufaktur Ceper, 2022)
Composite is a combination of two or more different materials that are combined with the aim of getting better strength from the constituent materials. This study aims to identify the effect of variations in fiber volume fraction and determine the proportion of the best volume fraction based on the tensile and flexural strength values in hybrid composites reinforced with EFB fiber and bagasse fiber. The composite manufacturing process was carried out using the compression molding method with variations in fiber volume fraction 6:14, 8:12, 10:10, 12:8 and 14:6. The tests carried out were density testing (ASTM C271) and tensile strength (ASTM D3039 ). The highest tensile strength test results were obtained at fiber volume fraction 8:12 with a value of 17.39 Mpa.